Analisis Kepuasan Implementasi Bot WhatsApp Pelayanan Permohonan Surat Akademik UNU Lampung Menggunakan Metode PIECES - Muhammad Haris Hermanto; Hadi Nurma Dwi Saputra; Ableo Swares; Sri Lestari (JTRISTE, 2026)
Academic administration is a core service in higher education institutions that involves a high level of interaction with students, particularly in managing academic documents. Along with the increasing number of students and the demand for fast, accurate, and responsive services, Universitas Nahdlatul Ulama (UNU) Lampung developed a WhatsApp Bot for academic document request services based on Node.js without using the official WhatsApp API. However, the implementation of a non-official API-based chatbot requires a comprehensive readiness evaluation that considers not only technical aspects but also non-technical dimensions. This study aims to analyze user satisfaction and implementation readiness of the WhatsApp Bot for academic document services at UNU Lampung using the PIECES method. This research employs a descriptive quantitative approach, with data collected through observation and questionnaires. The questionnaire was designed based on the PIECES indicators, namely Performance, Information, Economics, Control, and Service, and involved 52 student respondents. The data were analyzed by calculating the average satisfaction score for each indicator. The results show that all PIECES indicators fall within the satisfied category, with average scores of 4.04 for Performance, 4.00 for Information, 4.11 for Economics, 4.08 for Control, and 3.99 for Service. The overall average satisfaction score of 4.04 indicates that the implementation of the WhatsApp Bot is satisfactory and feasible as an academic service system. The Economics indicator achieved the highest score due to significant time and cost efficiency benefits, while the Service indicator obtained the lowest score, mainly due to limitations in automated service interaction. Overall, the WhatsApp Bot improves the efficiency and effectiveness of academic document services and is suitable for further development.